Pengaruh Perilaku Pemimpin dan Komitmen Karyawan Terhadap Prestasi Kerja Karyawan Pada Puskesmas Desa Aro Kecamatan Muara Bulian - Niki Kosasih (Universitas Batanghari Jambi, 2019)
The title of this study is the Effect of Leader Behavior and Employee Commitment on Employee Work Achievement at Village Aro Health Center, Muara Bulian District. The Effect of Leader Behavior and Employee Commitment is treated as an independent variable and Employee Work Performance is treated as the dependent variable. This study aims to (1) To clarify the description of leader behavior (2) To clarify the picture of employee commitment (3) To clarify the description of employee work performance (4) To analyze the influence of Leader Behavior and Employee Commitment on Work Performance of Village Aro Community Health Center Muara Bulian District . The method used is the survey method. The population as well as samples in this study were 43 respondents. Data collection is done by distributing questionnaires to respondents. Data were analyzed using descriptive statistical analysis and analysis involving the determination of the regression coefficient correlation test. The results of this study indicate that (1) Leader behavior variables based on questions the average value of the 5 indicator indicators amounted to 3.48, it can be seen the respondent answered agree. (2) The leader behavior variable based on the question of the average value of the 5 question indicators is 3.34 so that the respondents can answer neutral. (3) Work performance variables based on the questions of the average value of the 5 question indicators amounted to 3.48, so the respondents answered neutral. (4) Leader Behavior and Employee Commitment have a positive and significant effect on Employee Performance at the Aro Village Health Center, Muara Bulian District, which is 76.6%.